Analysis of the Use of Language in the Development of the Tourism Industry - Fazalani, Runi; Saputra, Gede Adistana Wira; Purwahita, Anak Agung Ayu Ribeka Martha; Simanjuntak, Vitalia Hanako Murni (Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to determine the use of Language in developing the tourism industry. This research is qualitative descriptive by using primary data directly obtained from data sources, namely the use of Indonesian in the tourism industry in Bali Jimaran, which was taken documentarily by the researcher. The data collection techniques used are documentation and observation. This research results in the use of Indonesians in the tourism industry. As mentioned, Indonesia is dynamic, so the Language is alive, changing, and developing. The reason for using foreign languages is that Indonesians and many foreign tourists use buses. Although using foreign languages makes it easier to communicate with foreign tourists, the correct and standard use of English is a priority. The most commonly used words are beach, tourist, and opening. Three things will happen if foreign languages, especially English, play a more critical role in tourism than Indonesian. (1) the occurrence of a change in one's way of thinking and one's social control. With this, unconsciously, the use of foreign language terms in the world of tourism has changed the mindset of its use, (2) the emergence of different speech styles and the content of the conversation. This is said to be not uncommon in people who speak two different languages; (3) their interest in appreciating and learning Indonesian is decreasing.